Cultivated cure, regenerated affliction: Encounters with ALS and stem cell regeneration in India (Medicine Anthropology Theory, 2017)
In this think piece, I interrogate the notion of cure in order to address the idea of disease. My intention is to show how emerging biotechnological modalities that cultivate an idea of ‘cure as regeneration’ dislocate expert knowledge, descriptions of disease, and its representation into contested new terrains. In approaching disease from the vantage point of the ‘cultivated cure’ I seek to trouble our commonsense view of afflictions. Drawing on ethnographic data from a longitudinal project engaged in mapping stem cell technologies in India, I conceptualize how ‘cure as regeneration’ reanimates the figures of disease and medical knowledge. I take up Veena Das’s challenging query: is it necessary to define terms – illness, disease, diagnosis, health – that defy neat characterization?